Profitability of sergestid shrimp (Acetes spp.) catching using saludan and sungkit in Tigbauan, Iloilo - Ferrer, Alice Joan G. (Danyag : Journal of Humanities and Social Sciences, 2003)
The paper determines the profitability of hipon catchin using saludan (filter bagnet) and sungkit (skimming net) in Tigbauan, Iloilo using cost and return analysis. Specifically, the paper describes the socio-economic characteristics of sungkit and saludan owners, describes hipon catching operation, determines costs incurred and revenues earned, and identifies the problems encountered in hipon catching. Twenty saludan owners and thirteen sungkit owners from Barangays Barroc, Atabayan, Baguinguin, Namocon and Tanpael, Tigbuan, Iloilo were interviewed. Data on volume of catch-sold, operating costs incurred, and price received are based on the last week operations prior to interview. Results show that hipon catching using saludan and sungkit yields positive pure economic profit per-catching-trip. On the average, sungkit owners receive P1,445.54, while saludan owners receive P51.92. The problems encountered in hipon catching include bad weather, limited fishing area; high operating costs incurred low price of catch, and dependency of laborers.